Moving up the Quality ladder? EU-China Trade Dynamics in Clothing - Hylke Vandenbussche; Francesco Di Comite; Laura Rovegno; Christian Viegelahn (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
We apply a simple method to study the relative quality of Chinese versus European products exported in the clothing sector after the end of the Multi-Fiber Arrangement. Based on the model of Foster et al (2008), we interpret the relative change of export prices and quantities sold in narrowly defined product categories as an indicator of quality shifts. Using UN Comtrade data we find that European varieties exported to the US typically sell for a higher price than identical Chinese varieties exported to the US, but this price gap is narrowing. Despite rising prices, Chinese varieties are gaining market share. This opposite movement of relative prices and quantities sold in the same destination market, are a strong indication of China moving up the quality ladder in its clothing exports relative to the EU. While European ?core? products in clothing are stable over time, Chinese exports show strong product dynamics with exit and entry of new ?core? products every year and ?core? products changing rapidly. Both China and the EU export in every product category, resulting in an almost perfect product overlap with almost no products being exported by only one of the two.
Keywords: 330; Bekleidungsindustrie; Außenhandel; Produktqualität; EU-Staaten; China